Gravity measurements in Jameson Land and neighbouring parts of East Greenland - Forsberg, René (Meddelelser om Grønland. Geoscience, 1986)
In the summer of 1982 a regional gravity survey of Jameson Land and adjacent East Greenland areas was carried out by the Danish Geodetic Institute. The purpose of this survey was primarily to contribute to the ongoing efforts to evaluate the hydrocarbon potential of the area. Together with gravity data from supplementary surveys in 1983 and 1984, a total of 379 new gravity stations has been established in the central East Greenland area. The gravity station spacing ranges from 5 to 30 km, most dense in southern and central Jameson Land, where a small area around J. P. Koch Fjeld was covered with a station spacing down to 1 km to investigate local structural disturbances in the area. In the paper results of the surveys are given, including details of the processing of the raw gravimeter readings, barometric elevations and terrain correction computations. Additionally the results of earlier, unpublished surveys in the Scoresby Sund and Mesters Vig regions are presented. Based on available onshore and offshore gravity data, Bouguer anomaly maps are outlined for Jameson Land and for the central East Greenland region 69°N to 73°N, 30°W to 19°W. The gravity data of the region show very large anomalies, with Bouguer anomalies varying from 90 mgal on the continental shelf to -180 mgal near the edge of the Inland Ice at the centre of the Caledonian fold belt. This variation is consistent with general isostatic principles, and probably primarily indicates changes in crustal thickness. Over the Jameson Land post-Caledonian sedimentary basin a smooth anomaly picture is found, with an E-W trending high crossing the central part of the area, and SSW-NNE trending lows and highs in the southern part, probably closely related to overall basin structure and basement geology. In the local area around J. P. Koch Fjeld a small positive anomaly seems to be associated with the structural disturbances, thus probably indicating shallow, relatively high-density rocks within the sedimentary sequence.